TRPM8 indicates poor prognosis in colorectal cancer patients and its pharmacological targeting reduces tumour growth in mice by inhibiting Wnt/β‐catenin signalling. (17th October 2022) - Pagano, Ester; Romano, Barbara; Cicia, Donatella; Iannotti, Fabio A.; Venneri, Tommaso; Lucariello, Giuseppe; Nanì, Maria Francesca; Cattaneo, Fabio; De Cicco, Paola; D'Armiento, Maria; De Luca, Marcello; Lionetti, Ruggiero; et al.
Abstract: Background and Purpose: Transient receptor potential melastatin type‐8 (TRPM8) is a cold‐sensitive cation channel protein belonging to the TRP superfamily of ion channels. Here, we reveal the molecular mechanism of TRPM8 and its clinical relevance in colorectal cancer (CRC). Experimental Approach: TRPM8 expression and its correlation with the survival rate of CRC patients was analysed. To identify the key pathways and genes related to TRPM8 high expression, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses were conducted in CRC patients. TRPM8 functional role was assessed by using Trpm8 −/− mice in models of sporadic and colitis‐associated colon cancer. TRPM8 pharmacological targeting by WS12 was evaluated in murine models of CRC. Key Results: TRPM8 is overexpressed in colon primary tumours and in CD326 + tumour cell fraction. TRPM8 high expression was related to lower survival rate of CRC patients, Wnt–Frizzled signalling hyperactivation and adenomatous polyposis coli down‐regulation. In sporadic and colitis‐associated models of colon cancer, either absence or pharmacological desensitization of TRPM8 reduced tumour development via inhibition of the oncogenic Wnt/β‐catenin signalling. TRPM8 pharmacological blockade reduced tumour growth in CRC xenograft mice by reducing the transcription of Wnt signalling regulators and the activation of β‐catenin and its target oncogenes such as C‐Myc and Cyclin D1 . Conclusion and Implications: Human data provide valuable insights to propose TRPM8 as a prognostic marker with a negative predictive value for CRC patient survival. Animal experiments demonstrate TRPM8 involvement in colon cancer pathophysiology and its potential as a drug target for CRC. Abstract :